1997
DOI: 10.1117/12.274242
|View full text |Cite
|
Sign up to set email alerts
|

<title>Laser-induced damage of fused silica at 355 and 1064 nm initiated at aluminum contamination particles on the surface</title>

Abstract: Contamination particles of controlled size and shape were deposited onto 1.14 cm thick fused silica windows by sputtering Al through a mask. The particles were 1 µm thick circular dots, 10 to 250 µm in diameter. Al shavings were also deposited on the windows to investigate the effects of particle-substrate adhesion. The silica windows were then illuminated repetitively using a 3-ns, 355 nm and an 8.6-ns, 1064 nm laser. The tests were conducted at near normal incidence with particles on the input and output sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…9 -17 Such diffraction effects have become increasingly more noticeable in the fields of laser processing 7 and laser-induced damage. 5,6,18,19 Diffraction produces downstream light-intensity modulations that are often noticed in the image plane when particles of dust land upon optical components. When such contam-ination particles fall in the path of a powerful laser beam, they can sometimes initiate laser-induced damage 5,6,9,20 -22 or trigger self-focusing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 -17 Such diffraction effects have become increasingly more noticeable in the fields of laser processing 7 and laser-induced damage. 5,6,18,19 Diffraction produces downstream light-intensity modulations that are often noticed in the image plane when particles of dust land upon optical components. When such contam-ination particles fall in the path of a powerful laser beam, they can sometimes initiate laser-induced damage 5,6,9,20 -22 or trigger self-focusing.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] A range of different types of optical material ͑e.g., fused silica, KDP, hafnia-silica multilayers, Nd-doped laser glass͒ was investigated for determination of the contamination level that could be tolerated during peak intensity operation on the laser beams of the National Ignition Facility and the Laser Méga Joule. 5,22 The initial goal of the study reported here was to quantify systematically the drop in laser-induced-damage threshold of fused silica at 355 nm caused by contamination particles ͑various contaminant sizes, shapes, and materials͒ on input and output surfaces. As the study progressed and damage morphologies were being characterized, it became clear that diffraction of light by input-surface obscurations, and sometimes by rare bulk inclusions, contributes to decreasing the damage threshold of output surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The results are depiced in Figure 3 in which (a)-(c) show the residual manufacturing defects left on the surface of the glass through polishing (Genin, Feit, Kozlowski, Rubenchik, Salleo, & Yoshiyama, 2000;Honig, Norton, Hollingsworth, Donohue, & Johnson, 2005;Salleo, Genin, Yoshiyama, Stolz, & Kozlowski, 1998). On the other hand, Figure 3(d)-(f) show microexplosions triggered by irradiation of surface contaminants of the fused-quartz cuvettes using the high pulse repetition-rate laser (Genin, Feit, Kozlowski, Rubenchik, Salleo, & Yoshiyama, 2000;Honig, Norton, Hollingsworth, Donohue, & Johnson, 2005;Salleo, Genin, Yoshiyama, Stolz, & Kozlowski, 1998;Genin, Michlitsch, Furr, Kozlowski, & Krulevitch, 1997). To further investigate the damage results shown in Figure 3, open aperture z-scan studies were carried out using empty damaged fused-quartz cuvettes at both 76MHz and the pulse-picked repetition rate of 152Hz and the results are displayed in Figure 4.…”
Section: Resultsmentioning
confidence: 94%
“…Ample evidence exists that particulate contamination initiates damage on both bare and coated optical surfaces in the presence of high intensity laser light [1]. More recently, it has been found that flashlamp light is sufficient to create aerosols within laser amplifier cavities and that the these aerosol particles subsequently settle onto laser amplifier slabs and initiate pitting damage to the optical surface [2].…”
Section: Damage Related Reasons For Establishing High Cleanliness Reqmentioning
confidence: 99%